Testing Measurement Invariance of Academic Self-Efficacy Scale for Singapore, Spain and Turkey - Ozen Yildirim; Eren Can Aybek (Journal of Education in Science, Environment and Health)
A scale that does not measure the same structure in different cultures should not be used in the cross-cultural comparison-based studies. The validity of the scales should be tested primarily for the countries. In this study, as the evidence of validity of the Programme for International Student Assessment (PISA) 2015 science self-efficacy scale, the measurement invariance has been tested for different cultures.  As determined in scientific studies, general self-efficacy is focused on more and this should be examined in academic self-efficacy known to be to student learning and achievement. In the analysis of the data, the measurement model is initially tested. Then, the measurement invariance is tested with a series of analysis. As a result, the scale confirms a unidimensional structure for each country. However, it has provided partial measurement invariance. This indicates that item-based analysis should be conducted.